Qanat System at Bidar District in Karnataka, India - Raghubans, Kishore (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
A preliminary investigation on hydraulic system for revitalization of qanat system and emphasis model study at Bidar, Karnataka in India and in future such studies to be carried out to the other water structures.  HYDRO Nepal JournalJournal of Water, Energy and EnvironmentIssue: 17, July 2015